Regional Aspects in a New Engineering Way of Thinking Development of Bachelors of Techniques and Technology; Advances in Intelligent Systems and Computing; Vol. 907 : Going Global through Social Sciences and Humanities: A Systems and ICT Perspective (GGSSH) - Egorova G. I. Galina; Loseva N. I. Natalya; Egorov A. N. Andrey; Belyak E. L. Elena; Demidova O. M. Olga Mikhailovna (Advances in Intelligent Systems and Computing book series, 2019)
Title screen